Professional ethics among quantity surveyor in construction industry of Sarawak / Bartimeus Jerangkang - Jerangkang, Bartimeus (2021)
The construction industry plays a vital role in helping the national development in socio-economic and employment. Ethics is usually about right and wrong and touches on morality issues. Their professional body governs ethical behaviour through the codes of conduct. Investment funds on a large scale are invested in this industry as an opportunity for unethical activities such as corruption. This research aims to gauge opinion on various ethical issues in Sarawak's construction industry activities from a Quantity Surveyor's perspective. Quantitative research is adopted, which is the data collection method is through literature review and electronic questionnaires. There are 81 participants that are willing to participate in this research. From the findings, Quantity Surveyors in Sarawak agree that nepotism is the ethical issue they can experience, project delay is the most serious effect of ethical issues, and punish offenders, or rigorous prosecution is the most effective way to prevent these issues. From the conclusion, almost all the Quantity Surveyors have experienced ethical issues during their duty. It is recommended that to create an ethical industry, all the construction players must take action, not only Quantity Surveyor.